Assessing EFL Learners Ability in the Recognition And Production of Homophones - Asst. Instructor Elaf Riyadh Khalil (College of Education for Women, 2019)
This study deals with the orthographic processing ability of homophones which can account for variance in word recognition and production skills due to phonological processing. The study aims at: A)Investigating whether the students can recognize correct usage and spelling comprehension of different homophones by using appropriate word that overlapped in both phonology and orthography. B)Assessing spelling production word association to the written form of the homophone in the sentence comprehension task. To achieve these aims, two tests have been conducted and distributed on 50 students at first stage at the College of Education(Ibn-Rushd) for the academic year 2010-2011. The two tests are exposed to a jury of experts for the purpose of ascertaining their validity. The split-half reliabilities (Spearman-Brown corrected) from this task were .93 and .82, respectively to calculate their reliability coefficient. The results show that there are statistical differences between the two tests: the recognition test and the production test show that the testees have achieved better performance in the recognition test(75%)than in the production test (25%) .